Research of visual attention networks in deaf individuals: a systematic review - Gioiosa Maurno, Nahuel; Phillips-Silver, Jessica; Daza González, María Teresa (Frontiers in Psychology, 2024)
The impact of deafness on visual attention has been widely discussed in previous research. It has been noted that deficiencies and strengths of previous research can be attributed to temporal or spatial aspects of attention, as well as variations in development and clinical characteristics. Visual attention is categorized into three networks: orienting (exogenous and endogenous), alerting (phasic and tonic), and executive control. This study aims to contribute new neuroscientific evidence supporting this hypothesis.This paper presents a systematic review of the international literature from the past 15 years focused on visual attention in the deaf population. The final review included 24 articles.